(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The digital age has reshaped our world, fundamentally impacting our understanding of ourselves and our place within it. This paper explores the human condition in the digital age through the lens of existentialist philosophy. We will examine key concepts like freedom, responsibility, authenticity, and meaning-making in the context of our ever-evolving relationship with technology. By analyzing the opportunities and challenges presented by the digital landscape, we aim to gain a deeper understanding of the existential anxieties that arise and offer potential pathways for navigating this complex terrain.